Environmental challenges posed by veld fires in fragile regions: The case of the Bulilima and Mangwe districts in southern Zimbabwe - Ernest Dube (AOSIS, 2023)
This original research confronted challenges to environmental management and sustainability posed by veld fires in the Bulilima and Mangwe Districts of Matabeleland in the South Province in southern Zimbabwe. Veld fires have affected the fauna and flora, polluted air and water, and destroyed livelihoods. The study aimed at establishing challenges to environmental sustainability posed by veld fires, identifying the type of environment upon which veld fires have impacted, analysing legal issues and other interventions surrounding the control of veld fires and suggesting new control measures for veld fires. A qualitative research design and quota sampling were used. The study involved 30 participants. Data was collected through a questionnaire, an interview guide and participant observation. Challenges to environmental management and sustainability posed by veld fires include property damage, reduced soil fertility, destruction of vegetation, air and water pollution and destruction of wildlife. Most veld fires are a result of human actions that emanate from the disposal of cigarettes, the burning of vegetation when preparing fields, the use of fire by hunters, smoking out bees and the making of fires by motorists along highways. The government should consider reviewing the current environmental statues. Fireguards should be wide enough to lessen veld-fire impact. Lastly, veld-fire campaigns and rehearsals should be run on a regular basis. It is hoped that this work would make a significant contribution through improving the current thinking about environmental management and sustainability, thereby benefiting policy makers, practitioners and stakeholders.